Kosovo : Institutions and Policies for Reconstruction and Growth. (International Monetary Fund, 2002)
Kosovo was placed under temporary UN administration in 1999, and a final political settlement remains pending. Since that time, however, the province has developed the instruments and institutions necessary to formulate and implement an independent economic policy. This paper provides an overview of Kosovo's economy and its institutions to date, including those of self-government, and discusses the main economic policy challenges currently facing the province.